Investigation of the impact of the GaN cap layer on DC and RF performance in N-polar AlGaN/GaN HEMTs - Das, Chumki; Mazumdar, Kaushik (Frontiers in Physics, 2025)
In this paper, we investigated the logic and RF performance of nanostructure N-polar AlGaN/GaN high-electron mobility transistors (HEMTs) with and without GaN cap layer. It’s found that devices without the GaN cap layer exhibit superior performance, the maximum drain current density of 0.99 mA/μm at VGS = 2 V and a corresponding on-state resistance (Ron) of 0.88 Ω·mm. The GaN HEMT without GaN cap layer leads to a peak transconductance of 0.75 S/mm at VDS = 3 V. Varying the drain doping concentration significantly affects both the current density and transconductance. At a doping concentration (ND) of 1022 cm−3, the device without GaN cap layer achieves a maximum current density of 0.98 mA/μm at VDS = 1 V, and the maximum cut-off frequency (fT) of 183.8 GHz at VDS = 3 V. These findings highlight the potential of N-polar AlGaN/GaN HEMTs without the GaN cap layer for high-power, high-frequency, and micro- and nano-electromechanical system (M/NEMS) sensors applications.